Rhetoric as Media’s Persuasive Strategy Toward Readers in the Headline on Market Issues - Mulya, Rina; Sumarsih, Sumarsih; Dirgeyasa, I Wayan (Language Circle: Journal of Language and Literature, 2024)
Headline is intended to highlight the main point or category of the news article. They commonly attract readers using strong and emotive words and attention-grabbing vocabulary. This situation made journalists often manipulate the headline news to ensure its appeal and allure to the reader using some linguistic device. This research discussed the rhetoric on market issues in headline news of CNBC Indonesia and to examine the types of rhetoric used on market issues. Descriptive qualitative research is applied in this research. The data sources were headline news on market issues and taken from the website of CNBC Indonesia. There were 300 selected headlines in total around November 2022 – February 2023. In addition, documentation was employed in collecting the data. The data were analyzed by using Van Dijk’s Critical Discourse Analysis framework (2015). The findings showed that there are 25 types of rhetoric. It was identified that rhetoric was not limited to alliteration, rhyme, parallelism, hyperbole, understatement, metaphor, and metonymy (Van Dijk, 1991). Other rhetorical devices like personification and onomatopoeia were discovered in the headline. It was also found a headline incorporating two or more rhetoric, for instance, the combination of hyperbole and rhyme, which called as compound rhetoric.